Parametric Study on Dynamic Response of Fiber Reinforced Polymer Composite Bridges - Woraphot Prachasaree; Attapon Sangkaew; Suchart Limkatanyu; Hota V. S. GangaRao (International Journal of Polymer Science)
Because of high strength and stiffness to low self-weight ratio and ease of field installation, fiber reinforced polymer (FRP) composite materials are gaining popularity as the materials of choice to replace deteriorated concrete bridge decks. FRP bridge deck systems with lower damping compared to conventional bridge decks can lead to higher amplitudes of vibration causing dynamically active bridge deck leading serviceability problems. The FRP bridge models with different bridge configurations and loading patterns were simulated using finite element method. The dynamic response results under varying FRP deck system parameters were discussed and compared with standard specifications of bridge deck designs under dynamic loads. In addition, the dynamic load allowance equation as a function of natural frequency, span length, and vehicle speed was proposed in this study. The proposed dynamic load allowance related to the first flexural frequency was presented herein. The upper and lower bounds’ limits were established to provide design guidance in selecting suitable dynamic load allowance for FRP bridge systems.